Tolerating CD47 - Jeffrey S. Isenberg; Enrique Montero (Clinical and Translational Medicine, 2024)
Abstract Cluster of differentiation 47 (CD47) occupies the outer membrane of human cells, where it binds to soluble and cell surface receptors on the same and other cells, sculpting their topography and resulting in a pleiotropic receptor‐multiligand interaction network. It is a focus of drug development to temper and accentuate CD47‐driven immune cell liaisons, although consideration of on‐target CD47 effects remain neglected. And yet, a late clinical trial of a CD47‐blocking antibody was discontinued, existent trials were restrained, and development of CD47‐targeting agents halted by some pharmaceutical companies. At this point, if CD47 can be exploited for clinical advantage remains to be determined. Herein an airing is made of the seemingly conflicting actions of CD47 that reflect its position as a junction connecting receptors and signalling pathways that impact numerous human cell types. Prospects of CD47 boosting and blocking are considered along with potential therapeutic implications for autoimmune diseases and cancer.